Hydrodynamic performance of pile-supported OWC-type structures as breakwaters : an experimental study - He, Fang (2014)
Oscillating water column (OWC) is one of the mechanisms for extracting wave energy from ocean waves. In this study, we experimentally investigated the hydrodynamic performance of a pile-supported OWC structure as a breakwater, for which the air-flow through a small opening in the top cover contributes to energy extraction from waves and reduction in transmission coefficients. The effects of relative breadth, draught and opening conditions on wave reflection, wave transmission, energy dissipation and the pressure fluctuation inside the OWC chamber were examined. Compared with other types of pile-supported breakwaters, the hydrodynamic performance of the pile-supported OWC structure is remarkable and the pile-supported OWC structure has the potential for wave energy utilization.